If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(4b + 3) + (9b + -6) = 0 Reorder the terms: -2(3 + 4b) + (9b + -6) = 0 (3 * -2 + 4b * -2) + (9b + -6) = 0 (-6 + -8b) + (9b + -6) = 0 Reorder the terms: -6 + -8b + (-6 + 9b) = 0 Remove parenthesis around (-6 + 9b) -6 + -8b + -6 + 9b = 0 Reorder the terms: -6 + -6 + -8b + 9b = 0 Combine like terms: -6 + -6 = -12 -12 + -8b + 9b = 0 Combine like terms: -8b + 9b = 1b -12 + 1b = 0 Solving -12 + 1b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 1b = 0 + 12 Combine like terms: -12 + 12 = 0 0 + 1b = 0 + 12 1b = 0 + 12 Combine like terms: 0 + 12 = 12 1b = 12 Divide each side by '1'. b = 12 Simplifying b = 12
| 22=3x^2-18x | | 4p/8=9 | | x^2-32=8x | | 6(3-4k)= | | 9(2+X)=8(2+X) | | n-3n=4 | | 4.30x=3.75x+4 | | a^3-7a^2-8a= | | .85x+.05(2-x)=.10(-31) | | a^3-7a^2-8= | | -10x+3x= | | 9g/3=6 | | 7x-3=78-2 | | x^2+32=4 | | 9-7(x+3)=5-6x | | h(x)=9x^5-12x^3+6x | | 25(4x+1)=9(10x+25) | | 9/10=99/x | | 4.0x+2=3.75x+4 | | 30=k(8) | | m+12.3=-4.1 | | 24x^2+24+6= | | 4p^2+4p-360= | | 5x+10-c=10 | | x-3/4=3/4 | | m+122.3=-4.1 | | 6x-8=2+9x | | 3=-3(7-2n)-4(n-7) | | 3(v+1)=2(v-8) | | 3234=2.1(x)+4.2(3x) | | 4b^2+36b= | | logx=10.23 |